Usos do livro didático de História: entre prescrições e táticas - Araci Rodrigues Coelho (2009)
The object of this research are the uses that the teachers of the Fundamental Teaching / Ensino Fundamental first segment say to be doing of the History didactic book most issued by the PNLD 2004: História com Reflexão / History with Reflection (Coleção Horizontes ). Such an object is inserted in the crossing of two study fields: that of History Teaching and that of the the Didactic Book. Owing to the object complexity, we have adopted the theoretical-methodological perspective that joins the qualitative researches presuppositions and procedures, in dialogue with other fields, mainly those from the Sociology of Education and from the History of Education and, specifically, that of the History of the book and that of the Reading Practices. Upon this analytical perspective, taking into account the criticism to the didactic books analysis that starting in the 1980s reveal the ideology conveyed by those books, in special those of History or Social Studies, which do not take into account the knowledge mobilized in those supports, neither the subjects and contexts involved in their teaching and learning. We have investigated specifically the uses of this book distributed by the PNLD, by 4th and 5th grade school teachers, in order to describe and analyze the informed uses of this book, seeking to know their experiences with this didactic materials and the meaning they created in their teaching practices. Once outlined the personal and professional conditions of the teachers under research, it was possible to see that usually they use the LdH HcR in a context where the limits between Geography and History are badly defined, although ten years ago, with the LDB 1996, these disciplines officially returned to the [Ensino Fundamental] Fundamental Teaching first grades curriculum, dismembered from the Social Studies discipline that have been in effect so far. This research shows that the teachers, through their speech, deceive or even go against the PNLD prescriptions, using the LdH HcR that has the authoral project format (Rojo 2006) and that seek to assume the role of the schoolastic History innovations messenger usually as archive, where they take passages, texts, images and ideas in order to teach History. Under this meaning, we conclude that the teachers say that they use, besides this LdH, the Regional LdH distributed by the PNLD 2004, other History didactic books coming from other PNLD choice processes, in addition to several publications wether directed to the school or not and, still, other materials produced within the school by themselves or their colleagues. It is also evidenced that the teachers declare to use these didactic materials starting from different combinations, which end by producing original History teaching and learning proposals and that bear as the main purpose to break the emptied perspective brought by the Social Studies. Finally, we conclude that although the schools under survey had received the History didactic book best evaluated by the PNLD 2004, this fact in itself hasnt granted that the History teaching in these schools has been renewed according to the new History didactic books proposals. Therefore, this paper refers other researchers studies concerning History teaching and seeks to contribute with new investigations, showing that besides granting good didactic materials, it is necessary to invest massive and systematically not only on the material resources but also and moreover on the continual education and working conditions in our schools and their professionals.